Debt, Investment, Slaves : Credit Relations in East Feliciana Parish, Louisiana, 1825-1885 - Kilbourne, Richard Holcombe (Book collections on Project MUSE., 1995)
A thorough survey of parish mortgage records and other manuscript collections led to the conclusion that most credit relationships, collateralized and uncollateralized, were grounded in slave property as opposed to land or other forms of wealth. Uncollateralized debt was directly dependent on the relative wealth of parish residents, and the bulk of most portfolios consisted of slaves. Emancipation and the Civil War occasioned a monumental credit implosion from which the local economy never recovered, at least for the remainder of the 19th century. Kilbourne make.